Socialisation and executive MBA programmes - Elkin, Graham (Cranfield School of Management, 1991)
This paper explores the socialisation processes experienced by MBA students entering business schools. Reports from MBA students at the Otago (New Zealand) and Cranfield (United Kingdom) university business schools are reviewed using the Pascale' model of socialisation. The common experience of business school students is then compared with the corporate experiences reported by Pascale. Implications for the socialisation process at business schools and for the teachers of organisational Behaviour are discussed.